Towards Achieving Professional Merit: An Overview - Mohammed Masoud AL-ABDULLAH (Communications of International Proceedings, 2022)
Involvement in the stages of education and learning is the first gate of life in a journey that extends to the selection of individuals their professions and determines what they are, whether practical or scientific, governmental, or private. There are also requirements which could be enhanced to ensure that individuals have successful access and performance quality in their careers, starting from the level of Competency through scientific life and the Abilities to execute, until gaining Experiences during the years of working and, activating skills of all kinds to achieve distinction towards achieving Professional Merit. However, from the researcher multiple experiences of college admission affairs at the Faculty of Architecture and Planning and later being the Dean of the same college involved with recruiting faculties, as well as later being the Dean for the Deanship of faculty and staff affairs at the university level; choice and selection of people in these cases have shown a great similarity between them.  The researcher aims to explore, and emphasis concepts and criteria associated with people's selection in positions need Professional Merit level. It can be said that these concepts' outcomes rely heavily on the developed analytical mind and actual related practices.
Keywords: Analytical mind; Competency; Ability; Experience; Professional Merit